Compreensão e produção de orações relativas em crianças com e sem desvio fonológico - Glória, Yasmin Alves Leão (2017)
This study aimed to analyze the performance of children with phonological disorder (PD) and typical language development (TLD) between the ages of 4 years to 8 years and 11 months in the skills of comprehension and production of relative clauses, and to verify if there is difference in the comparison between the groups, and to verify if there is difference in the comparison between the ages. The relevance of this work is given therefore, the domain of this grammatical structure is of extreme importance for the development of oral language. It is worth mentioning that there are few studies in Brazilian Portuguese regarding the acquisition of relative clauses, as well as the acquisition of these structures in the, being extremely important to study the domain of this type of clauses in the population with TLD, more specifically the comparison of ages, since they are late acquisition in children's language. The comparison with PD is relevant, since there are studies that prove that children with alterations in the phonological level of the language may present deficits in the lexical and syntactic organization, involving these grammatical elements. For the selection of the sample, phonoaudiological evaluations, such as the Phonological Assessment of the Child (PAC), Orofacial Miofunctional Assessment (AMIOFE), Articulatory Examination and assessment of oral language observational and through a logical sequence were applied, hearing screening. After these evaluations, the children were selected for data collection, forming a total of 53 children, in which 26 children had PD and 27 children had TLD, in both groups, the tests of relative sentences were applied, based on the Adapted Test by Costa et al., 2009, for the evaluation of the Test of Production was used the test of preference already for the test of Comprehension of Relative Clauses was used the Test of Identification of Images. The results were applied descriptive and inferential statistics. Thus, we can observe a statistically significant difference in relation to the mean of the percentage of correct answers in the tasks of producing relative of subject and object (PRSO), with better performance of the children with TLD in relation to children with PD and did not obtain a significant statistical difference in the tasks of relative compression of subject (CRS), we obtained a statistically significant difference in the object relative comprehension task (CRO), with a better performance of children with PD in relation to children with TLD. In the comparison between the means of correctness by age there was no statistically significant difference. It is concluded that children with TLD presented better performance in relative subject clauses (ORS) relative to relative object clauses (ORO), and that both are acquired gradually during evolution. Children with PD presented inferior performance in the tasks of PRSO with greater difficulties in ORO, although there were no statistically significant differences between the comparison of the means of the ages, it was noticed greater correctness in children older than the younger ones.